Efektivitas Faktor Terapeutik dan Dinamika Kelompok Sebagai Intervensi Problem Anggota : Systematic Literature Review - Fadhilatin Nashihah; Muslikah (Universitas Muria Kudus, 2026)
Guidance and Counseling (BK) services currently face an increasingly complex spectrum of member issues, ranging from academic barriers to personal-social behavioral crises. This study aims to synthesize the mechanisms of therapeutic factors and group dynamics in transforming various member problems through a comprehensive literature review. The method employed is a Systematic Literature Review (SLR) following the Francis & Baldesari protocol. Literature searches were conducted through Google Scholar, SINTA, DOAJ, and Garuda databases within the 2019-2025 publication range. Based on strict selection criteria, 11 credible scientific journal articles were selected for analysis. The results indicate that the dominant problems intervened are anxiety as well as low academic motivation and resilience. Therapeutic factors such as group cohesion, universalism, and self-efficacy enhancement were identified as primary catalysts for behavioral change. The integration of counseling techniques (REBT, SFBT, and digital media) proved highly effective in optimizing group dynamics, as evidenced by significant score increases in post-test results. As a recommendation, BK practitioners are encouraged to integrate creative media and focus on strengthening Yalom's therapeutic factors within group service designs to achieve accountable and sustainable behavioral transformation.